Outbreak of Nerium oleander poisoning in llamas in Jujuy, Argentina: clinical, pathological, and diagnostic insights - Vera, Tomas Anibal (2026)
This case report describes an outbreak of Nerium oleander poisoning in llamas in Jujuy, Argentina. The outbreak occurred after ingestion of pruned, dry plant material, resulting in a mortality rate of 27% (3/11 animals). Affected animals exhibited respiratory distress, tachycardia, mucus discharge from the anus, vulva, and nostrils, diarrhea, and acute nonspecific abdominal pain on palpation within 24 hours of ingestion. Deaths occurred within 48 hours of the onset of clinical signs. Necropsy findings included acute pulmonary congestion and edema, linear whitish streaks on the epicardial surface, and subendocardial hemorrhages. Plant fragments were identified in the first and second gastric compartments (C1 and C2). Histopathological examination revealed multifocal cardiomyocyte degeneration and necrosis. These findings are consistent with the well-documented cardiotoxic effects of N. oleander in various animal species. The rapid onset of clinical signs and fatal outcomes in affected animals underscores the high toxicity of this plant. This incident highlights the importance of raising awareness and implementing preventive measures among livestock producers, particularly regarding the presence of toxic ornamental plants in agricultural environments.